Succinic acid improves crop chemical components by regulating soil chemical properties, microbes and metabolites - Li, Dian-long; Liu, Qiang; Zhao, Rui-juan; Gao, Wei-chang; Zheng, Xin-rong; Zhou, Shi-yu; Cai, Kai; Jiang, Xian-jun (Frontiers in Microbiology, 2025)
IntroductionSmall molecule metabolites can act as soil conditioners to improve the soil environment and thereby promote crop growth. Like many other components of root exudates, succinic acid not only contributes to plant growth and stress resistance but also influences microbial growth in soil, thereby participating in the carbon cycle. Succinic acid is believed to act as a signaling molecule that bridges the host plant and microorganisms during their interactions. However, the mechanism by which succinic acid affects microbes, metabolites and their interaction in soil remains unclear.MethodsHigh-throughput sequencing and pseudotargeted metabolomics techniques were applied for exploring the effects of succinic acid in tobacco-planting soil and corresponding tobacco chemical composition.ResultsThe addition of succinic acid improved the soil chemical properties for increasing the available potassium, total nitrogen, total phosphorus and total potassium, and had a positive impact on soil fertility. In the microbial communities, fungi were more sensitive to succinic acid than bacteria. The relative abundance of Proteobacteria in the bacterial community was significantly decreased, while that of Chloroflexi was significantly increased. The relative abundances of Actinobacteriota and Acidobacteriota also showed a decreasing trend. The relative abundances of Ascomycota and Basidiomycota in the fungal community increased significantly, while the relative abundance of Chytridiomycota decreased significantly. The microbial function prediction indicated that 0.4% succinic acid may affected the nutrients and carbon-nitrogen cycles. In the soil metabolomics, the absolute contents of monosaccharide, disaccharide, sugar alcohol and trehalose in soil metabolites increased significantly. The 47 characteristic metabolites were significantly enriched in amino acid metabolism and carbohydrate metabolism. Correlation analysis showed that soil microbes were mainly positively correlated with amino acids and sugars. In addition, the relative abundances of monosaccharide, disaccharide and sugar alcohol increased in tobacco leaf, while alkaloid and amino acid decreased for improving the tobacco chemical composition.ConclusionThis study demonstrated that the addition of succinic acid affected soil chemical property, microbial communities and the composition of soil metabolites, and then improved crop chemical components.